Synthesis and crystal structures of palladium complexes based on $α $-amino-oximes derived from ($R$)-limonene and their application in allylic alkylation of 1,3-dioxo compounds - Homrani, Yasmina; El Amrani, Mohamed Amin; Loxq, Pauline; Capet, Frédéric; Suisse, Isabelle; Sauthier, Mathieu (Comptes Rendus. Chimie)
Coordination compounds Pd(L1)Cl$_{2}$, Pd(L2)Cl$_{2}$, and Pd(L3)Cl$_{2}$ have been synthesized from optically pure $α $-amino-oxime ligands L1–L3 based on $(R)$-limonene. Structures of the new palladium complexes are characterized and described by NMR spectroscopy and X-rays. These $α $-amino-oxime ligands were then evaluated in the palladium-catalysed allylation of 1,3-dioxo compounds.